Pengelolaan Media Sosial dalam Penyebaran Informasi oleh Humas Pemerintahan - Nabila Rahmaniya; Neni Yulianita (UNISBA Press, 2023)
Abstract. In accordance with Presidential Instruction No. 9 of 2015 and PERMAN RB No. 83 of 2012, public relations for government agencies must convey public information through social media. Seeing this, Bandung City Public Relations tried to enforce the policy. Based on the statement above, it can be seen that the purpose of this research is to (1) describe the process of packaging information on government public relations social media; (2) Describe the management of social media by government public relations in loading information from the public; (3) Describe the management of institutional messages by government public relations with the public; (4) Analyze the need to build public opinion through social media. The subjects of this research are employees who are involved in social media management. This study uses a constructivist paradigm, qualitative methods, and The Circular Model for Social Communication. The results of this study are the process of packaging information on Bandung City Public Relations social media consisting of monitoring issues, agenda setting, production, and post-production. Regarding the loading of information from the public, Public Relations of the City of Bandung provides access for the people of the City of Bandung to provide information with a percentage of 20%. In managing institutional messages, Bandung City Public Relations coordinates with OPD, the manager of LAPOR! in 151 sub-districts and 30 sub-districts, and SKPD in Bandung City. Meanwhile, to build public opinion, Bandung City Public Relations partnered with 200 journalist. Abstrak. Sesuai dengan Instruksi Presiden Nomor 9 Tahun 2015 dan PERMAN RB No. 83 Tahun 2012, humas instansi pemerintahan harus menyampaikan informasi publik melalui media sosial. Melihat hal ini, Humas Kota Bandung mencoba untuk meemberlakukan kebijakan tersebut. Berdasarkan pernyataan di atas, dapat diketahui bahwa tujuan penelitian ini adalah untuk (1) Mendeskripsikan proses pengemasan informasi pada media sosial humas pemerintahan; (2) Mendeskripsikan pengelolaan media sosial oleh humas pemerintahan dalam memuat informasi dari publiknya; (3) Mendeskripsikan pengelolaan pesan lembaga oleh humas pemerintahan dengan publiknya; (4) Menganalisis diperlukannya membangun opini publik melalui media sosial. Subjek penelitian ini adalah pegawai yang terlibat dalam pengelolaan media sosial. Penelitian ini menggunakan paradigma konstruktivis, metode kualitatif, dan The Circular Model for Social Communication. Hasil penelitian ini adalah proses pengemasan informasi pada media sosial Humas Kota Bandung terdiri dari monitoring isu, agenda setting, produksi, dan pascaproduksi. Terkait pemuatan informasi dari publiknya, Humas Kota Bandung memberikan akses bagi masyarakat Kota Bandung untuk memberikan informasinya dengan persentase sebesar 20%. Dalam pengelolaan pesan lembaga, Humas Kota Bandung berkoordinasi dengan OPD, pengelola LAPOR! di 151 kecamatan dan 30 kelurahan, dan SKPD Kota Bandung. Sedangkan, untuk membangun opini publik, Humas Kota Bandung bermitra dengan 200 wartawan.